Development of NiZn Ferrites Doped with Co for Low Power Losses at High Frequencies (10 MHz) and High Temperatures (>80 °C) - Stefanos Zaspalis; Georgios Kogias; Vassilios Zaspalis; Eustathios Kikkinides; Elisabeth Rauchenwald; Christoph Vogler; Kevin Ouda (Magnetochemistry)
Polycrystalline nickel–zinc (NiZn) ferrites are widely used in high-frequency applications due to their excellent magnetic properties such as low power losses, high magnetic permeability, and adequate saturation induction. However, data on their power loss behavior at 10 MHz, particularly at elevated temperatures, remain limited in the literature. This study investigates the magnetic performance of Co-doped NiZn ferrites at 10 MHz, under varying induction fields (3–10 mT) and temperatures (20–120 °C), with a focus on reducing high-temperature losses. Ferrite samples were synthesized using the conventional mixed oxide method and systematically varied in composition (Fe, Co content and Ni/Zn molar ratio). Key findings reveal that the incorporation of cobalt significantly enhances high-temperature performance by shifting resonance frequencies, attributed to increased domain wall pinning. Samples with optimized compositions and processing demonstrated power losses at 10 MHz, 10 mT and 25 °C, 100 °C and 120 °C as low as 310 mW cm−3, 1233 mW cm−3 and 1400 mW cm−3, respectively, with relative initial permeabilities exceeding 80 at these temperatures. These results provide insights into the design of high-frequency magnetic components and highlight strategies to minimize high-temperature losses.